2016
DOI: 10.15376/biores.11.2.4342-4352
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Nano-Fibrillated Cellulose as a Coating Component in Paper Coating

Abstract: This work investigates nano-fibrillated cellulose (NFC) as a component in mineral pigment paper coating. In this work, bleached Eucalyptus pulp was pretreated by TEMPO (2,2,6,6-tetramethyl-1-piperdinyloxy)-mediated oxidation. The oxidized pulp was then isolated to obtain NFC by sonication. Aqueous coating colors consisting of calcium carbonate, clay, carboxylated butadiene-styrene latex, additives, and NFC were prepared. The rheology of the coating colors and the surface properties of paper coated with NFC con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The suitability of NFC as rheological modifiers in the aqueous coating formulation for paper products has been extensively evaluated, for example, using TO‐NFC as rheological modifiers, calcium carbonate, and kaolin as pigments, carboxylic butadiene–styrene latex as synthetic binders, and polyamine polyurea resin as water‐resistant agents. [ 336 ] The presence of TO‐NFC increased the viscosity at low shear rates, but TO‐NFC had no obvious influence on viscosity at high shear rates due to the superior shear‐thinning behavior of TO‐NFC. The enhanced low shear rate viscosity was advantageous for sagging prevention.…”
Section: Emerging Applications Of Cnms As Rheology Modifiersmentioning
confidence: 99%
“…The suitability of NFC as rheological modifiers in the aqueous coating formulation for paper products has been extensively evaluated, for example, using TO‐NFC as rheological modifiers, calcium carbonate, and kaolin as pigments, carboxylic butadiene–styrene latex as synthetic binders, and polyamine polyurea resin as water‐resistant agents. [ 336 ] The presence of TO‐NFC increased the viscosity at low shear rates, but TO‐NFC had no obvious influence on viscosity at high shear rates due to the superior shear‐thinning behavior of TO‐NFC. The enhanced low shear rate viscosity was advantageous for sagging prevention.…”
Section: Emerging Applications Of Cnms As Rheology Modifiersmentioning
confidence: 99%
“…Treatment of cellulose with the relatively stable free-radical species 2,2,6,6tetramethylpiperidine-1-oxyl radical (TEMPO) in the presence of an oxidizing agent has become a popular route to the production of NFC under reduced energy requirements (Lasseuguette 2008;Lasseuguette et al 2008;Johnson et al 2009;Hirota et al 2010;Besbes et al 2011a,b;Ishii et al 2011;Loranger et al 2012a,b;Mishra et al 2012;Araki 2013;Benhamou et al 2014;Fukuzumi et al 2014;Kekalainen et al 2014aKekalainen et al , 2015Lindström and Aulin 2014;Mohtaschemi et al 2014a,b;Nechyporchuk et al 2014Nechyporchuk et al , 2015Bettaieb et al 2015;Jowkarderis et al 2015;Martoia et al 2015Martoia et al , 2016Rees et al 2015;Pääkkönen et al 2016;Xu et al 2016). In addition to facilitating the fibrillation of the material, TEMPO-mediated oxidation also imparts a negative charge to the surfaces (at pH values near to or above the pKa value of the carboxylic acids) (Hirota et al 2010;Fukuzumi et al 2014;Isogai 2015).…”
Section: Chemical Assistance To Fibrillationmentioning
confidence: 99%
“…In aqueous coating formulations for paper products, NFC appears to provide favorable attributes of water retention and thickening (Dimic-Misic et al 2013a;Gruneberger et al 2014;Zhou et al 2014;Rautkoski et al 2015;Salo et al 2015;Xu et al 2016). Dimic-Misic et al (2013a reported that NFC tends to act as both viscosity enhancer and water-binding agent, whereas conventional thickeners used in coating formulation, such as CMC, appear to serve more as viscosity enhancers.…”
Section: Coating Formulationmentioning
confidence: 99%
“…Should the resulting combination of measurements be related to an unacceptably low yield, recycling for further fibrillation would be triggered, automating the common decision in a typical batch process. Extractives can be determined gravimetrically after a solid-liquid extraction with organic solvents, while the consistency index, directly proportional to the apparent viscosity, would require a rheometer (Xu et al 2016;Serra-Parareda et al 2021c).…”
Section: On the Input Parametersmentioning
confidence: 99%